2010
DOI: 10.1155/2010/501521
|View full text |Cite
|
Sign up to set email alerts
|

Partial Bell‐State Analysis with Parametric down Conversion in the Wigner Function Formalism

Abstract: We apply the Wigner function formalism to partial Bell-state analysis using polarization entanglement produced in parametric down conversion. Two-photon statistics at a beam-splitter are reproduced by a wavelike description with zeropoint fluctuations of the electromagnetic field. In particular, the fermionic behaviour of two photons in the singlet state is explained from the invariance on the correlation properties of two light beams going through a balanced beam-splitter. Moreover, we show that a Bell-state … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…In both cases the non-null correlations correspond to different polarization components, the only difference being the minus sign that appears in |Ψ − . On the other hand, the case β = ∓π/2 and κ = π (β = −π/2, κ = 0) corresponds to the description of ∓|Φ + (|Φ − ), where the horizontal (vertical) component of a beam is correlated with the horizontal (vertical) component of the conjugated one [16].…”
Section: The Sixteen Hyper-bell States In the Wrhpmentioning
confidence: 99%
See 3 more Smart Citations
“…In both cases the non-null correlations correspond to different polarization components, the only difference being the minus sign that appears in |Ψ − . On the other hand, the case β = ∓π/2 and κ = π (β = −π/2, κ = 0) corresponds to the description of ∓|Φ + (|Φ − ), where the horizontal (vertical) component of a beam is correlated with the horizontal (vertical) component of the conjugated one [16].…”
Section: The Sixteen Hyper-bell States In the Wrhpmentioning
confidence: 99%
“…In the Wigner formalism, by putting κ = β = 0 in Eqs. (13) to (16), we obtain the following four beams in order to compactly describe the four states |Ψ + ⊗ |ψ ± and |Ψ + ⊗ |φ ± :…”
Section: Discrimination Of the Momentum Bell-statesmentioning
confidence: 99%
See 2 more Smart Citations
“…In [19] it is shown that those inequalities may be used for a case of entangled photons for a quantum optical experiment. The contemporary review of this topic and the corresponding references may be found in [20]. However, that class of inequalities is not suitable for testing in HEP experiments.…”
Section: Introductionmentioning
confidence: 99%